Program Studi Agribisnis Pangan - Rizky Pambagio; Sutarni Sutarni; Marlinda Apriyani; Fitriani Fitriani (Universitas Galuh, 2023)
This study aims to determine the level of income, the use of production factors for organic rice production, and the level of organic rice farming scale in Pringsewu Regency. This research was conducted from December 2021 to May 2022. Sampling used census sampling, namely taking the entire population as the research sample and the number of respondents as many as 33 people. Data analysis uses income analysis, Cobb-Douglas function analysis, and the level of business scale (return to scale). The results showed that organic rice farming was profitable and feasible to run because it had an R/C ratio of 2.64. Production factors of land area, seeds, manure, labor, and POC have a simultaneous effect on organic rice production with a percentage of production variation of 97.7%. The organic rice production process in Pringsewu Regency is at an increasing level of business (increasing return to scale), meaning that if an addition is made to the use of production factors, it will produce additional production with a larger proportion.